Integrating Jigsaw and Picture-and-Picture Cooperative Learning in Sprint Instruction: A One-Group Pre–Post Study in an Indonesian Madrasah Aliyah - Febri Sapta Pradana; Putri Cicilia Kristina; Bambang Hermansah (Journal of Pedagogy and Education Science, 2026)
Sprint-running instruction in school physical education requires students to coordinate key technique phases (start, acceleration, arm action, and posture) while maintaining motivation, yet teacher-centred drills can reduce active learning time, feedback, and peer modeling. This study evaluated the feasibility of implementing a combined cooperative-learning approach (Jigsaw and Picture-and-Picture) in sprint-running lessons and examined whether learning outcomes improved from pretest to posttest. A one-group pretest–posttest design was conducted with 25 students from MAN 1 OKI (Ogan Komering Ilir, South Sumatra, Indonesia). The intervention was delivered across four class meetings during September–October 2025 by integrating peer-teaching through home/expert groups with sequenced visual representations of sprint technique. Learning outcomes were assessed using a composite score covering cognitive (multiple-choice test), affective (observation), and psychomotor (performance rubric) domains. Mean scores increased from 62.8 (SD = 11.78) at pretest to 67.6 (SD = 8.72) at posttest, and a paired-samples t-test showed a significant difference, t(24) = 3.806, p = 0.001, with a moderate-to-large within-subject effect (Cohen’s dz ≈ 0.76). The model was feasible to implement within regular PE lessons and offers a practical option to increase student involvement and clarify technique through step-by-step visuals. However, because the design lacked a comparison group, the improvement cannot be attributed solely to the intervention; future multi-site studies with control groups are recommended.